KELAYAKAN BISNIS PADA USAHA SNACK BAWANG FAJWA DI KECAMATAN PURWOSARI KABUPATEN BOJONEGORO ( TINJAUAN PADA ASPEK LEGALITAS USAHA, SYARIAH DAN KEHALALAN ) - Nadhifah, Nurul Ahillatun; Ulfa Nikmatus Sa'adah (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
This study aims to analyze business feasibility studies in terms of business legality aspects, sharia, and halal, case studies in the Snack Bawang Fajwa Snack Kec Purwosari business, Bojonegoro Regency. The method used in this study uses qualitative methods, while the type of research uses qualitative descriptive types with data collection methods in several ways namely interviews, direct observations, and previous literature reviews. The results obtained from this study are in the application of Haspel business legality, it has been applied to Mrs. Fatimah's efforts by applicable laws, so the conclusions of the products issued by Mrs. Fatimah can be guaranteed legality and in the application of sharia and halal aspects In this business has been applied in terms of the type of product, product raw materials and product distribution are by sharia principles, and have also received halal certificates.